Assessment of chromosomal instabilities in the form of micronuclei in couples with recurrent pregnancy loss - Sujithaa Nagarajan MD; Suma Hottigoundar; Latha Chaturvedula (Golestan University Of Medical Sciences, 2023)
Background: The present study aims to assess chromosomal instabilities between fertile couples and couples with recurrent pregnancy loss (RPL) and the causative relation of chromosomal instabilities with RPL. Methods: A case-control study was performed with a study sample of 27 couples with a history of RPL who attended the Department of Obstetrics and Gynecology, Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER) and twenty-seven healthy fertile couples as controls. The procedure done was Cytokine Blocked Micronucleus Assay (CBMN). After obtaining consent and details of the couple, 3 ml of heparinized blood was collected from cases and controls. Cases comprising couples with RPL (gestational age ≤ 24 weeks) were included, and couples with a history of diabetes mellitus, thyroid disorders, and hypertension were excluded. Among cases, women with a history of two or more two spontaneous abortions ≤ 24 weeks of gestation were selected. Blood was collected and assessed from both male and female partners. The lymphocytes were cultured per the standard protocol and were screened as the number of micronuclei per 1000 binucleate cells under X 200 magnification in CBMN. Results: Chromosomal instabilities in the form of micronuclei in cases were found to be 7.52±3.99 and 0.07±0.26 in controls (p˂0.05). A statistically significant difference was revealed among those with and without chromosomal instability. Conclusion: Chromosomal instability serves as a significant causative factor for those couples leading to pregnancy losses